Paper and mobile-based education to improve knowledge and self-efficacy on exclusive breastfeeding - Aufanida Zakia; Sita Helida Dwi Rahma; Titik Kuntari (JHeS (Journal of Health Studies), 2025)
Knowledge and self-efficacy are important elements of exclusive breastfeeding success. Educational interventions with various media are conducted to improve exclusive breastfeeding. The study aimed to explain the effectiveness of education using a combination of leaflets (paper), e-leaflets, and videos with WhatsApp media to increase knowledge and self-efficacy of breastfeeding. The research design was a pre and post-test without a control group and involved a group of 20 pregnant women in the second and third trimesters. The intervention was carried out for 4 weeks. Knowledge measurement and Prenatal Breastfeeding Self-Efficacy Scale (PBSE) scores were conducted before and after the intervention. The intervention significantly improved maternal knowledge (pre-test: 17.9 ± 1.447; post-test: 18.55 ± 1.234; p=0.046) but did not significantly increase PBSE scores (pre-test: 63.5 ± 7.54; post-test: 65.35 ± 9.19; p=0.327). Education should employ diverse approaches and media, targeting both mothers and their immediate social environment, particularly families.